Preliminary Characterization of Structural and Rheological Behavior of the Quinoa Hyperprotein-Defatted Flour - Ortiz-Gómez, Vicente; Nieto-Calvache, Jhon Edinson; Roa-Acosta, Diego Fernando; Solanilla-Duque, Jose Fernando; Bravo-Gómez, Jesús Eduardo (Frontiers in Sustainable Food Systems, 2022)
The technological functionality of proteins is an indispensable property in food development due to their stabilizing capacity in different dispersed systems (foams, gels and emulsions). The functional properties of proteins are related to physical and chemical parameters that influence the behavior of proteins in food systems during processing, storage and consumption. The structural and rheological properties of three quinoa hyperprotein flours (without defatting, WD, chemically defatted, CD and mechanically defatted, MD) were evaluated. Flow index (n) values were significantly different (p<0.05) which was associated with changes in protein or starch structures due to solvent treatments or heating of the flour during pressing. Besides, a strong dependence of the consistency index (k) on shear rate was observed. For dispersions at a concentration of 12% (w/v), CD and WD had a setback value significantly lower than MD. The viscosity peak was affected by the presence of lipid molecules. Greater change was evident in the β-sheet structure (1610 and 1625 cm-1) and β-turn (1685 and 1695 cm-1). The changes identified in these structures were associated with the defatting treatment. Consequently, the intensity ratio 2920/1633 was more sensitive to changes in the fat content of the flours. It was shown that defatting conditions increase the protein adsorption kinetics. It was found that defatting conditions increase the protein adsorption kinetics and that the viscoelastic properties of the protein increased when the flour had a lower fat content. The objective of this work was to study the effect of two types of defatting of hyperprotein quinoa flour on the physicochemical and rheological properties.